ANALISIS KESULITAN SISWA DALAM MENULIS PUISI NARATIF PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS IV - Wahyuni, Tiara Indah Sri; Gunawan, Dani; Mulyana, Herdi (IPI Press, 2021)
The focus in this research is to analyze how the results of writing narrative poetry by students and the difficulties experirnced by students. This approach uses a qualitative approach with a descriptive method, where the subjects are teachers and foutrh grade students. The data collection process was carried out by the method of tests and interviews. Based on the results of the study it was concluded that: 1) the results of writing narrative poetry for fourth grade students consisting of themes, message, diction and rhymes still relatively simple from 24 students there are 10 students who belong to the “good” criteria, 3 students belong to the “Enough” criteria, and 11 students fall into the “Less” criteria. 2) difficulties experienced by students, namely in determining the title and content of the poem according to the theme, difficulty in determining the mandate, difficulty in determining diction and rhyme. The difficulty that is classified as the strongest is on the elements of diction and rhyme, and the lightests difficulty is in determining the mandate.